Pre-oxidized fiber aerogel felt and preparation method thereof
Through technical means such as plasma treatment, chemical branches, and adding coupling agents, the binding strength of the air gel layer of pre -oxygen wire gas gel felt and the uniformity of the pore distribution of the pre -oxygen silk layer is improved, and the existing technology is solved, and the existing technology is solved. The problem of unstable performance and insufficient insulation performance realizes higher mechanical strength and thermal insulation performance.
Patent Information
- Application Number
- CN202411383366.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
AI Technical Summary
The existing pre-oxygen wire aerogel felts have uneven pore distribution, low mechanical strength, and low permeability of aerogel and pre-oxygen wire layers, resulting in unstable performance and insufficient thermal insulation performance.
Measures through plasma treatment, chemical branches and binders or coupling agents significantly improve the binding strength of the gas gel layer and pre -oxygen wire, and improve the uniformity of pore distribution through accurately controlling the amount of spray coating and spray parameters. Essence
It significantly improves the mechanical strength and binding strength of gas gel felt, improves performance consistency and thermal insulation performance, reduces thermal conductivity, and is suitable for high temperature protection.
Smart Images

Figure BDA0005070437630000141 
Figure BDA0005070437630000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation materials, and in particular to a pre-oxidized silk aerogel felt and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles and electronic products, the demand for high-performance thermal insulation materials is growing. As an advanced thermal insulation material, pre-oxidized silk aerogel felt has broad application prospects.
[0003] Preoxidized silk aerogel felt is an aerogel material prepared by preoxidized silk fiber reinforcement technology, which is prepared by process steps such as impregnation sol, gelation, modification and supercritical drying. This material has low thermal conductivity, good flexibility and burn-through resistance, high tensile strength and natural fire resistance, and is suitable for thermal insulation and flame retardancy between battery modules of new energy passenger vehicles, thermal insulation protection of 3C electronic products and other fields.
[0004] Preoxidized fiber is the primary raw material of carbon fiber. It has low strength (about 300MPa) and almost no conductivity. It is mainly used for product insulation and has flame retardant, water repellent and anti-melting properties. Preoxidized fiber aerogel felt combines the advantages of preoxidized fiber and aerogel. Compared with traditional aerogel felt, it has better mechanical properties and thermal insulation properties at the same density, and the thermal conductivity can reach 0.023W / (m·K).
[0005] The pre-oxidized silk aerogel felt provided by the traditional preparation method has the following shortcomings:
[0006] 1) Uneven pore distribution: In the traditional preparation method, it is difficult to control the formation of pores during the sol-gel process, resulting in pores of different sizes and uneven distribution, which leads to unstable performance of aerogel felt, especially in terms of thermal conductivity and mechanical strength.
[0007] 2) Low mechanical strength: Due to the uneven pore distribution and the thin pore walls formed during the gelation process, the aerogel felt prepared by the traditional method has low mechanical strength, which limits its application in more fields.
[0008] 3) Low permeability between the aerogel layer and the base pre-oxidized silk layer: In the traditional preparation process, the bonding between the aerogel layer and the pre-oxidized silk layer is not tight enough and the permeability is low, resulting in low bonding strength between the two layers.
[0009] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0010] The technical problem to be solved by the present invention is to provide a pre-oxidized silk aerogel felt and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.
[0011] In order to solve the above technical problems, the technical solution adopted by the present invention is: in a first aspect of the present invention, a method for preparing a pre-oxidized silk aerogel felt is provided, comprising the following steps:
[0012] S1. Provide pre-oxidized silk felt;
[0013] S2, subjecting the pre-oxidized silk felt to plasma treatment, chemical grafting, and then modification of the coupling agent to obtain the pre-treated pre-oxidized silk felt;
[0014] S3, mixing tetraethyl orthosilicate, ethanol and a catalyst, stirring, then adjusting the pH value to 4-7 with sodium hydroxide or ammonia water, and then adjusting the viscosity to prepare an aerogel sol;
[0015] S4, spraying aerogel sol on the pre-treated pre-oxidized silk felt to obtain an intermediate product 1;
[0016] S5, immersing the intermediate product 1 in the aerogel sol to obtain the intermediate product 2;
[0017] S6, gelling the intermediate product 2 to obtain the intermediate product 3;
[0018] S7. The intermediate product 3 is subjected to supercritical drying treatment to obtain the final product: pre-oxidized silk aerogel felt.
[0019] Preferably, the thickness of the pre-oxidized fiber felt is in the range of 1 mm to 20 mm.
[0020] Preferably, step S2 specifically comprises:
[0021] S2-1, plasma treatment is performed on the pre-oxidized silk felt, the plasma power is 100-500W, and the treatment time is 5-20 minutes;
[0022] S2-2, adding the plasma treated pre-oxidized silk felt into a reactor, adding deionized water to immerse the pre-oxidized silk felt, and then adding 1%-5% of the mass of the pre-oxidized silk felt to the reactor (adding pure Silquest A-174 grafting agent, the added amount is 1%-5% of the pre-oxidized silk felt) and then reacting at 40-60°C for 2-4h; after the reaction is completed, taking out the pre-oxidized silk felt, washing it with deionized water, and drying it at 50-70°C for 1-4 hours;
[0023] S2-3. Add the preoxidized silk felt obtained in step S2-2 into a reactor, add deionized water to immerse the preoxidized silk felt, and then add 1%-5% of the mass of the preoxidized silk felt into the reactor, and react at 40-60°C for 1-4h. After the reaction is completed, take out the preoxidized silk felt, wash it with deionized water, and dry it at 50-70°C for 1-4h to obtain the pretreated preoxidized silk felt.
[0024] Preferably, step S3 specifically comprises:
[0025] According to the volume ratio of tetraethyl orthosilicate, ethanol and catalyst being 1:3-5:0.1-0.3, tetraethyl orthosilicate, ethanol and catalyst are mixed, stirred for 15-60 minutes, then the pH value is adjusted to 4-7 by sodium hydroxide, and then the viscosity is adjusted to 500-5000 mPa·s by polyethylene glycol 400 to prepare an aerogel sol;
[0026] The catalyst is a hydrochloric acid solution with a mass concentration of 30-38%.
[0027] Preferably, the volume ratio of tetraethyl orthosilicate, ethanol and catalyst is 1:3:0.1.
[0028] Preferably, the parameters for spraying the aerogel sol in step S4 are as follows:
[0029] The spraying amount is controlled at 10-100 g / m2, the sprayed aerogel sol particle size is controlled at 1-50 μm, the spray angle is controlled at 30-90°, the spray speed is controlled at 5-20 m / s, and the pressure is controlled at 0.2-0.8 MPa.
[0030] Preferably, step S5 specifically comprises: immersing the intermediate product 1 in the aerogel sol for 1-3 hours at a temperature of 30-50°C.
[0031] Preferably, step S6 specifically includes: placing the intermediate product 2 at a humidity of 40% to 60% and under inert gas protection for 12 to 48 hours to perform gelation treatment to obtain the intermediate product 3.
[0032] Preferably, the parameters of the supercritical drying treatment in step S7 are as follows: drying temperature is 200-300° C., pressure is 8-15 MPa, and drying time is 2-6 hours.
[0033] A second aspect of the present invention provides a pre-oxidized silk aerogel felt, which is prepared by the method as described above.
[0034] The beneficial effects of the present invention are:
[0035] (1) Significantly improve the bonding strength between the aerogel layer and the pre-oxidized silk layer
[0036] The present invention introduces active groups on the surface of the pre-oxidized silk felt by plasma treatment, chemical grafting, and adding a binder or coupling agent, thereby enhancing the affinity and bonding ability between the aerogel layer and the pre-oxidized silk layer, and significantly improving the bonding strength between the aerogel layer and the pre-oxidized silk layer. By precisely controlling the spraying amount and spraying parameters, the pore distribution uniformity of the aerogel felt is improved, thereby improving the mechanical strength. The scheme of the present invention can significantly improve the performance consistency of the aerogel felt, improve the mechanical strength and bonding strength, which makes the aerogel felt more stable and reliable during use, and is not prone to problems such as delamination.
[0037] (2) Reduce thermal conductivity and improve thermal insulation performance
[0038] The present invention ensures the stability and uniformity of the sol by precisely controlling the solution preparation parameters, such as the ratio of tetraethyl orthosilicate, ethanol and catalyst, and strictly adjusting the pH value and viscosity of the solution. At the same time, the spraying parameters and impregnation parameters are reasonably adjusted so that the aerogel can better cover the pre-oxidized silk felt and form a uniform structure. These measures work together to reduce the thermal conductivity. For example, the thermal conductivity in the embodiment can be as low as 0.019W / (m·K). In terms of thermal insulation performance, facing a high temperature of 1200°C, the temperature on the back of the aerogel felt in the embodiment is greatly reduced, which is about half of that in the control example, providing a more effective solution for high temperature protection in practical applications.
[0039] (3) Adapt to different thickness requirements and high flexibility
[0040] The preparation method of the present invention can select different thicknesses of pre-oxidized fiber felt according to different application requirements, and adjust the spraying parameters and impregnation parameters accordingly. For example, from the thickness of 1 mm in Example 1 to the thickness of 20 mm in Example 7, good performance can be achieved, which makes the aerogel felt of the present invention have higher flexibility and adaptability in applications in different fields. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0042] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0043] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0044] The present invention provides a pre-oxidized silk aerogel felt and a preparation method thereof, the method comprising the following steps:
[0045] S1. Provide pre-oxidized silk felt;
[0046] S2, subjecting the pre-oxidized silk felt to plasma treatment, chemical grafting, and then modification of the coupling agent to obtain the pre-treated pre-oxidized silk felt;
[0047] S3, mixing tetraethyl orthosilicate, ethanol and a catalyst, stirring, then adjusting the pH value to 4-7 with sodium hydroxide or ammonia water, and then adjusting the viscosity to prepare an aerogel sol;
[0048] S4, spraying aerogel sol on the pre-treated pre-oxidized silk felt to obtain an intermediate product 1;
[0049] S5, immersing the intermediate product 1 in the aerogel sol to obtain the intermediate product 2;
[0050] S6, gelling the intermediate product 2 to obtain the intermediate product 3;
[0051] S7. The intermediate product 3 is subjected to supercritical drying treatment to obtain the final product: pre-oxidized silk aerogel felt.
[0052] In a preferred embodiment, the MGYQ series pre-oxidized fiber felt purchased from Jiangsu Mige New Materials is selected, and the thickness of the pre-oxidized fiber felt ranges from 1mm to 20mm. The pre-oxidized fiber felt has certain flexibility and insulation properties, and can provide a support structure for the aerogel as an intermediate layer.
[0053] In a preferred embodiment, step S2 is specifically as follows:
[0054] S2-1. Plasma-treat the pre-oxidized fiber felt, for example, using the Openair-Plasma system of [Plasmatreat, with a plasma power of 100-500 W, more preferably 300 W, and a treatment time of 5-20 minutes, more preferably 15 minutes; by plasma treatment, active groups are introduced on the surface of the pre-oxidized fiber felt to improve its bonding ability with the aerogel layer.
[0055] S2-2. Add the plasma-treated preoxidized fiber felt into a reactor, add deionized water to submerge the preoxidized fiber felt, add 1%-5% (more preferably 3%) of the preoxidized fiber felt mass by Silquest A-174 grafting agent, and then react at 40-60°C (more preferably 50°C) for 2-4h (more preferably 3h); after the reaction, take out the preoxidized fiber felt, wash it with deionized water, and dry it at 50-70°C for 1-4 hours; ensure that the surface of the preoxidized fiber felt is dry.
[0056] S2-3. Add the preoxidized silk felt obtained in step S2-2 into a reactor, add deionized water to immerse the preoxidized silk felt, add 1%-5% (more preferably 3%) of the mass of the preoxidized silk felt, and react at 40-60°C for 1-4h. After the reaction is completed, take out the preoxidized silk felt, wash it with deionized water, and dry it at 50-70°C for 1-4h to obtain the pretreated preoxidized silk felt.
[0057] In a preferred embodiment, step S3 is specifically as follows:
[0058] According to the volume ratio of tetraethyl orthosilicate, ethanol and catalyst being 1:3-5:0.1-0.3, tetraethyl orthosilicate, ethanol and catalyst are mixed, stirred for 15-60 minutes (more preferably 30 minutes), then the pH value is adjusted to 4-7 (more preferably 5.5) by sodium hydroxide, and then the viscosity is adjusted to 500-5000 mPa·s by polyethylene glycol 400 to prepare an aerogel sol;
[0059] The catalyst is a hydrochloric acid solution with a mass concentration of 30-38%.
[0060] Precursor: Tetraethyl orthosilicate (TEOS) can be SilaneTek DMC from Evonik, solvent: Ethanol 96% from BASF can be used, hydrochloric acid 37% from Sigma-Aldrich can be used, and polyethylene glycol 400 can be Polyethylene Glycol 400 from Sigma-Aldrich can be used.
[0061] In a preferred embodiment, the volume ratio of tetraethyl orthosilicate, ethanol and catalyst is 1:3:0.1.
[0062] For stirring, an IKA stirrer model RW 20 basic can be used.
[0063] In a preferred embodiment, the parameters for spraying the aerogel sol in step S4 are as follows:
[0064] The spraying amount is controlled at 10-100 g / m2, the sprayed aerogel sol particle size is controlled at 1-50 μm, the spray angle is controlled at 30-90°, the spray speed is controlled at 5-20 m / s, and the pressure is controlled at 0.2-0.8 MPa.
[0065] When used in scenarios with high requirements for thermal insulation performance, a higher spraying amount can be selected, such as 80-100g / m2; for applications that are more sensitive to weight and cost, a lower spraying amount can be selected, such as 10-30g / m2. The aerogel sol particle size is more preferably 10-30μm. The spray angle can be selected according to the thickness and shape of the pre-oxidized silk felt. The spraying speed is adjusted according to the specific spraying equipment and sol characteristics. For thinner pre-oxidized silk felt, the spraying speed can be appropriately reduced, such as 5-10m / s; for thicker pre-oxidized silk felt, the spraying speed can be appropriately increased, such as 15-20m / s. The spraying equipment can use Krebs&Co.'s AirCap spraying system.
[0066] In a preferred embodiment, step S5 specifically comprises: immersing the intermediate product 1 in the aerogel sol for 1-3 hours, more preferably 2 hours, and controlling the immersion temperature at 30-50° C., more preferably 40° C. The equipment used for immersion can be Buchi's B-580 immersion container.
[0067] In a preferred embodiment, step S6 is specifically as follows: the intermediate product 2 is allowed to stand for 12-48 hours under the conditions of 40%-60% humidity and inert gas protection to perform gelation treatment to obtain the intermediate product 3. The gelation reaction is performed under specific conditions to form an aerogel with a three-dimensional network structure. The humidity is more preferably 50%, the inert gas is preferably nitrogen, and the standing time is more preferably 36 hours. The gelation reaction can be performed in a Buchi B-290 reaction chamber.
[0068] In a preferred embodiment, the parameters of the supercritical drying treatment in step S7 are as follows: the drying temperature is 200-300°C, more preferably 250°C; the pressure is 8-15MPa, more preferably 12MPa; the drying time is 2-6 hours, more preferably 4 hours. The supercritical drying technology is used to remove the solvent in the gel to avoid shrinkage and deformation of the gel. The gel is placed in a supercritical drying device for treatment, and the device can use the Supercritical Fluid Extraction System of Aaron Equipment.
[0069] The present invention aims to solve the problems of uneven pore distribution, low mechanical strength and low permeability of aerogel layer and pre-oxidized silk layer in the prior art. The preparation process provided by the present invention significantly improves the bonding strength between the aerogel layer and the pre-oxidized silk layer through measures such as plasma treatment, chemical grafting and the addition of a binder or coupling agent. By precisely controlling the spraying amount and spraying parameters, the uniformity of the pore distribution of the aerogel felt is improved, thereby improving the mechanical strength. The scheme of the present invention can significantly improve the performance consistency, mechanical strength and bonding strength of the aerogel felt.
[0070] In the present invention, the comprehensive application of plasma treatment, chemical grafting and the addition of coupling agent is the key to solving the low bonding strength between the aerogel layer and the pre-oxidized silk layer in the prior art. Active groups are introduced on the surface of the pre-oxidized silk felt by plasma treatment, which provides a basis for the action of chemical grafting and coupling agent. Chemical grafting further enhances the affinity between the pre-oxidized silk felt and the aerogel layer, while the coupling agent improves the interface compatibility. The three work together to significantly improve the bonding strength.
[0071] In the present invention, strictly controlling the ratio of tetraethyl orthosilicate, ethanol and catalyst, as well as the pH value and viscosity of the solution, is the key to ensuring the stability and uniformity of the aerogel sol. This enables the sol to better cover the pre-oxidized fiber felt and form a uniform aerogel structure in the subsequent process, thereby solving the problem of uneven pore distribution in the prior art.
[0072] In the present invention, the key to achieving uniform distribution and good penetration of aerogel on pre-oxidized fiber felt is to reasonably adjust the spraying parameters such as spraying amount, spray particle size, spray angle, spray speed and pressure, as well as the impregnation parameters such as impregnation time and temperature. This helps to improve the uniformity and density of the aerogel layer, thereby improving the mechanical strength and thermal insulation performance of the aerogel felt.
[0073] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0074] Example 1
[0075] S1. Provide pre-oxidized silk felt; select Jiangsu Mige New Material MGYQ series pre-oxidized silk felt with a thickness of 1mm.
[0076] S2, subjecting the pre-oxidized silk felt to plasma treatment, chemical grafting, and then modification of the coupling agent to obtain the pre-treated pre-oxidized silk felt:
[0077] S2-1, plasma treatment of pre-oxidized silk felt was performed using the Openair-Plasma system of Plasmatreat, with a plasma power of 100 W and a treatment time of 5 minutes;
[0078] S2-2, adding the plasma treated pre-oxidized silk felt into a reactor, adding deionized water to immerse the pre-oxidized silk felt, adding Silquest A-174 grafting agent accounting for 1% of the mass of the pre-oxidized silk felt, and then reacting at 40°C for 2h; after the reaction, taking out the pre-oxidized silk felt, washing it with deionized water to remove unreacted grafting agent and impurities, and drying it at 60°C for 2h;
[0079] S2-3. Add the preoxidized silk felt obtained in step S2-2 into a reactor, add deionized water to immerse the preoxidized silk felt, add 1% of the mass of Dow Corning silane coupling agent Z-6040, and react at 40°C for 1 hour. After the reaction is completed, take out the preoxidized silk felt, wash it with deionized water, and dry it at 60°C for 2 hours to obtain the pretreated preoxidized silk felt.
[0080] S3, according to the volume ratio of ethyl orthosilicate, ethanol and catalyst being 1:3:0.1, ethyl orthosilicate, ethanol and catalyst were mixed, stirred for 30 minutes using IKA stirrer model RW 20basic, then the pH value was adjusted to 4 with sodium hydroxide, and the viscosity was adjusted to 1000 mPa·s with polyethylene glycol 400 (Polyethylene Glycol 400 from Sigma-Aldrich), to prepare an aerogel sol;
[0081] The catalyst is a hydrochloric acid solution with a mass concentration of 37%, specifically Hydrochloric Acid 37% from Sigma-Aldrich, the ethyl orthosilicate is SilaneTek DMC from Evonik, and the ethanol is Ethanol 96% from BASF.
[0082] S4, spraying aerogel sol on the pre-treated pre-oxidized silk felt to obtain an intermediate product 1;
[0083] The parameters for spraying aerogel sol are as follows:
[0084] The spraying amount is controlled at 10g / m2, the particle size of the sprayed aerogel sol is controlled at 1μm, the spray angle is controlled at 30°, the spray speed is controlled at 5m / s, and the pressure is controlled at 0.2MPa. The AirCap spraying system of Krebs&Co. is used to ensure that the sol can be evenly covered on the surface of the pre-oxidized silk felt.
[0085] S5. Immerse the intermediate product 1 in the aerogel sol for 1 hour at a temperature of 30° C. Use a Buchi B-580 immersion container to allow the sol to fully penetrate into the pores of the pre-oxidized fiber felt to promote the gelation reaction.
[0086] S6. The intermediate product 2 was subjected to gelation reaction in a Buchi B-290 reaction chamber (drying chamber) under the conditions of 40% humidity and nitrogen protection. The gelation reaction time was 12 hours to obtain the intermediate product 3. Controlling the humidity and atmosphere of the reaction environment is conducive to forming a uniform aerogel structure.
[0087] S7. The intermediate product 3 is subjected to supercritical drying treatment to obtain the final product: pre-oxidized silk aerogel felt.
[0088] Aaron Equipment's Supercritical Fluid Extraction System was used for supercritical drying. The parameters of the supercritical drying treatment were as follows: drying temperature was 200° C., pressure was 8 MPa, and drying time was 2 hours.
[0089] After testing, the pore distribution of the pre-oxidized silk aerogel felt prepared in this embodiment is relatively uneven, the mechanical strength is improved to a certain extent, and the bonding strength between the aerogel layer and the pre-oxidized silk layer is average. The thermal conductivity is 0.025W / (m·K), and the thermal insulation performance is improved. Compared with the traditional preparation method, there is some progress in bonding strength and thermal insulation performance, but there is still room for improvement.
[0090] Example 2
[0091] This example is basically the same as Example 1, and the main differences are listed below.
[0092] In this example, the thickness of the pre-oxidized fiber felt is 3 mm.
[0093] In this example, the parameters for spraying the aerogel sol in step S4 are as follows:
[0094] The spraying amount is controlled at 20 g / m2, the particle size of the sprayed aerogel sol is controlled at 3 μm, the spray angle is controlled at 45°, the spray speed is controlled at 8 m / s, and the pressure is controlled at 0.3 MPa.
[0095] In this example, in step S5, the immersion time is 1.5 hours and the temperature is 35°C.
[0096] Example 3
[0097] This example is basically the same as Example 1, and the main differences are listed below.
[0098] In this example, the thickness of the pre-oxidized fiber felt is 5 mm.
[0099] In this example, the parameters for spraying the aerogel sol in step S4 are as follows:
[0100] The spraying amount is controlled at 30 g / m2, the particle size of the sprayed aerogel sol is controlled at 5 μm, the spray angle is controlled at 60°, the spray speed is controlled at 10 m / s, and the pressure is controlled at 0.4 MPa.
[0101] In this example, in step S5, the immersion time is 2 hours and the temperature is 40°C.
[0102] Example 4
[0103] This example is basically the same as Example 1, and the main differences are listed below.
[0104] In this example, the thickness of the pre-oxidized fiber felt is 8 mm.
[0105] In this example, the parameters for spraying the aerogel sol in step S4 are as follows:
[0106] The spraying amount is controlled at 40 g / m2, the particle size of the sprayed aerogel sol is controlled at 8 μm, the spray angle is controlled at 75°, the spray speed is controlled at 12 m / s, and the pressure is controlled at 0.5 MPa.
[0107] In this example, in step S5, the immersion time is 2.5 hours and the temperature is 45°C.
[0108] Example 5
[0109] This example is basically the same as Example 1, and the main differences are listed below.
[0110] In this example, the thickness of the pre-oxidized fiber felt is 10 mm.
[0111] In this example, the parameters for spraying the aerogel sol in step S4 are as follows:
[0112] The spraying amount is controlled at 50 g / m2, the particle size of the sprayed aerogel sol is controlled at 10 μm, the spray angle is controlled at 90°, the spray speed is controlled at 15 m / s, and the pressure is controlled at 0.6 MPa.
[0113] In this example, in step S5, the immersion time is 3 hours and the temperature is 50°C.
[0114] Example 6
[0115] This example is basically the same as Example 1, and the main differences are listed below.
[0116] In this example, the thickness of the pre-oxidized fiber felt is 15 mm.
[0117] In this example, the parameters for spraying the aerogel sol in step S4 are as follows:
[0118] The spraying amount is controlled at 70 g / m2, the particle size of the sprayed aerogel sol is controlled at 15 μm, the spray angle is controlled at 80°, the spray speed is controlled at 18 m / s, and the pressure is controlled at 0.7 MPa.
[0119] In this example, in step S5, the immersion time is 3.5 hours and the temperature is 55°C.
[0120] Example 7
[0121] This example is basically the same as Example 1, and the main differences are listed below.
[0122] In this example, the thickness of the pre-oxidized fiber felt is 20 mm.
[0123] In this example, the parameters for spraying the aerogel sol in step S4 are as follows:
[0124] The spraying amount is controlled at 90 g / m2, the particle size of the sprayed aerogel sol is controlled at 20 μm, the spray angle is controlled at 85°, the spray speed is controlled at 20 m / s, and the pressure is controlled at 0.8 MPa.
[0125] In this example, in step S5, the immersion time is 4 hours and the temperature is 60°C.
[0126] Comparative Example 1
[0127] S1. Provide pre-oxidized silk felt; select Jiangsu Mige New Material MGYQ series pre-oxidized silk felt with a thickness of 1mm.
[0128] S2, according to the volume ratio of ethyl orthosilicate, ethanol and catalyst being 1:3:0.1, ethyl orthosilicate, ethanol and catalyst are mixed, stirred for 30 minutes using IKA stirrer model RW 20basic, then the pH value is adjusted to 4 with sodium hydroxide, and the viscosity is adjusted to 1000 mPa·s with polyethylene glycol 400 (Polyethylene Glycol 400 from Sigma-Aldrich), to prepare an aerogel sol;
[0129] The catalyst is a hydrochloric acid solution with a mass concentration of 37%, specifically Hydrochloric Acid 37% from Sigma-Aldrich, the ethyl orthosilicate is SilaneTek DMC from Evonik, and the ethanol is Ethanol 96% from BASF.
[0130] S3, immersing the pre-oxidized fiber felt in the aerogel sol for 1 hour at a temperature of 30° C. A Buchi B-580 immersion container is used.
[0131] S4. The product of step S3 was subjected to gelation reaction in a Buchi B-290 reaction chamber (drying chamber) under the condition of 40% humidity and nitrogen protection. The gelation reaction time was 12 hours.
[0132] S5. The product of step S4 is subjected to supercritical drying to obtain a final product: pre-oxidized silk aerogel felt.
[0133] Aaron Equipment's Supercritical Fluid Extraction System was used for supercritical drying. The parameters of the supercritical drying treatment were as follows: drying temperature was 200° C., pressure was 85 MPa, and drying time was 2 hours.
[0134] After testing, the pore distribution of the pre-oxidized silk aerogel felt prepared in this example is very uneven, the mechanical strength is not significantly improved, and the bonding strength between the aerogel layer and the pre-oxidized silk layer is poor. The thermal conductivity is 0.035W / (m·K), and the thermal insulation performance is poor. Compared with Example 1, there are obvious deficiencies in terms of pore distribution uniformity, mechanical strength, bonding strength and thermal insulation performance. The comparison highlights the advantages of the technical solution of Example 1 of the present invention in these aspects.
[0135] Comparative Example 2
[0136] S1. Provide pre-oxidized silk felt; select Jiangsu Mige New Material MGYQ series pre-oxidized silk felt with a thickness of 1mm.
[0137] S2, subjecting the pre-oxidized silk felt to plasma treatment, chemical grafting, and then modification of the coupling agent to obtain the pre-treated pre-oxidized silk felt:
[0138] S2-1, plasma treatment of pre-oxidized silk felt was performed using the Openair-Plasma system of Plasmatreat, with a plasma power of 100 W and a treatment time of 5 minutes;
[0139] S2-2, adding the plasma-treated pre-oxidized silk felt into a reactor with an insulation jacket, adding Silquest A-174 grafting agent accounting for 1% of the mass of the pre-oxidized silk felt, and then reacting at 40°C for 2 hours; after the reaction, taking out the pre-oxidized silk felt, washing it with deionized water to remove unreacted grafting agent and impurities, and drying it at 60°C for 2 hours;
[0140] S2-3. Add the pre-oxidized silk felt obtained in step S2-2 into a reactor, add 1% of the mass of Dow Corning silane coupling agent Z-6040, and react at 40°C for 1 hour. After the reaction, take out the pre-oxidized silk felt, wash it with deionized water, and dry it at 60°C for 2 hours to obtain the pre-treated pre-oxidized silk felt.
[0141] S3, according to the volume ratio of ethyl orthosilicate, ethanol and catalyst being 1:3:0.1, ethyl orthosilicate, ethanol and catalyst were mixed, stirred for 30 minutes using IKA stirrer model RW 20basic, then the pH value was adjusted to 4 with sodium hydroxide, and the viscosity was adjusted to 1000 mPa·s with polyethylene glycol 400 (Polyethylene Glycol 400 from Sigma-Aldrich), to prepare an aerogel sol;
[0142] The catalyst is a hydrochloric acid solution with a mass concentration of 37%, specifically Hydrochloric Acid 37% from Sigma-Aldrich, the ethyl orthosilicate is SilaneTek DMC from Evonik, and the ethanol is Ethanol 96% from BASF.
[0143] S4, immersing the pre-treated pre-oxidized silk felt in the aerogel sol for 1 hour at a temperature of 30° C. A Buchi B-580 immersion container is used.
[0144] S5. The product of step S4 is subjected to gelation reaction in a Buchi B-290 reaction chamber (drying chamber) under the condition of 40% humidity and nitrogen protection. The gelation reaction time is 12 hours.
[0145] S6. Perform supercritical drying on the product of step S5 to obtain a final product: pre-oxidized silk aerogel felt.
[0146] Aaron Equipment's Supercritical Fluid Extraction System was used for supercritical drying. The parameters of the supercritical drying treatment were as follows: drying temperature was 200° C., pressure was 8 MPa, and drying time was 2 hours.
[0147] After testing, the pore distribution of the pre-oxidized silk aerogel felt prepared in this example is relatively uneven, the mechanical strength is improved to a certain extent, and the bonding strength between the aerogel layer and the pre-oxidized silk layer is improved. The thermal conductivity is 0.030W / (m·K), and the thermal insulation performance is improved, but compared with Example 1, there is still a gap in pore distribution uniformity, mechanical strength and bonding strength, and the thermal insulation performance is not as good as Example 1, which further reflects the importance of the spraying sol step in the technical solution of Example 1.
[0148] The following performance tests were performed on the pre-oxidized silk aerogel felts prepared in Examples 1-7 and Comparative Examples 1-2:
[0149] (1) Bonding strength between aerogel layer and pre-oxidized silk layer (gf / inch): 90° peel test, test standard:
[0150] ASTM D903 – Standard test method for evaluating the 90° peel strength of adhesives.
[0151] Test method:
[0152] Sample preparation:
[0153] The prepared pre-oxidized silk aerogel felt is cut into specimens of standard size (usually 25 mm×200 mm).
[0154] Prepare a stainless steel plate whose size should be larger than that of the specimen to ensure that the specimen can fit completely on the stainless steel plate.
[0155] Fitting sample:
[0156] The pre-oxidized silk aerogel felt was evenly attached to the stainless steel plate, ensuring that there were no bubbles or gaps between the aerogel layer and the stainless steel plate.
[0157] Use a roller or pressure roller to gently roll the sample to ensure that the aerogel layer is tightly bonded to the stainless steel plate.
[0158] Applying tape:
[0159] Stick a standard test tape (such as 3M 600 series tape, 25 mm in width) on the surface of the aerogel layer, making sure that the tape completely covers the aerogel layer and is firmly adhered.
[0160] Fixing the specimen:
[0161] Fix the stainless steel plate on the lower fixture of the 90° peel tester and ensure that the stainless steel plate is placed horizontally.
[0162] Fix the part of the aerogel layer with the tape on the upper fixture, ensuring that the peeling angle between the tape and the aerogel layer is 90°.
[0163] Peel test:
[0164] Start the 90° peel tester and perform the peel test at a constant speed (usually 300 mm / min).
[0165] Recording data:
[0166] The force required during the peeling process was recorded (in gf), and the average peel strength (in gf / inch) was calculated.
[0167] Result evaluation:
[0168] According to the test results, the bonding strength between the aerogel layer and the pre-oxidized silk layer was evaluated.
[0169] (2) Thermal conductivity
[0170] Test Standard: ASTM C177 – Standard Test Method for Measurement of Steady-State Heat Transfer Properties.
[0171] Test method:
[0172] Sample preparation: Cut the prepared pre-oxidized silk aerogel felt into specimens of standard size (usually 100 mm × 100 mm × 10 mm).
[0173] Hot plate method: The thermal conductivity is measured using the hot plate method. The sample is placed between a hot plate and a cold plate, and the temperatures of the hot plate and the cold plate are set to different constant values (for example, the hot plate temperature is 50°C and the cold plate temperature is 20°C).
[0174] Temperature measurement: Temperature sensors are installed on the upper and lower surfaces of the specimen to record the temperature difference between the hot plate and the cold plate.
[0175] Heat flow measurement: A heat flow meter is used to measure the heat flow through the specimen.
[0176] Calculate thermal conductivity: According to Fourier's law, calculate thermal conductivity:
[0177] k=q·L / ΔT
[0178] Where k is the thermal conductivity, q is the heat flux, L is the thickness of the sample, and ΔT is the temperature difference.
[0179] (3) Thermal insulation performance (1200°C, 30min back surface temperature)
[0180] Test Standard: ASTM E119 – Standard Test Method for Fire Resistance of Building Elements.
[0181] Test method:
[0182] Sample preparation: Cut the prepared pre-oxidized silk aerogel felt into specimens of standard size (usually 300 mm×300 mm).
[0183] In-furnace test: Fix the sample on the back plate of the refractory furnace, ensuring good contact between the sample and the back plate.
[0184] Heating conditions: The temperature of the refractory furnace was set to 1200°C and maintained for 30 minutes.
[0185] Temperature measurement: Install a temperature sensor on the back of the sample and record the temperature change within 30 minutes.
[0186] Result evaluation: Record and analyze the maximum temperature and temperature change curve on the back of the sample to evaluate the thermal insulation performance of the aerogel felt.
[0187] The test results are shown in Table 1 below:
[0188] Table 1
[0189]
[0190]
[0191] According to the test results in Table 1, the pre-oxidized silk aerogel felt prepared in Examples 1-7 has low thermal conductivity, excellent thermal insulation performance, and the bonding strength between the aerogel layer and the pre-oxidized silk layer is high, and these properties are significantly better than the comparative example. In a preferred embodiment, the bonding strength between the aerogel layer and the pre-oxidized silk layer can reach 110gf / inch (Example 7), which is much higher than the comparative example. This is attributed to the fact that the present invention uses plasma treatment, chemical grafting, and the addition of coupling agents and other technical means to introduce active groups on the surface of the pre-oxidized silk felt, thereby enhancing the affinity and bonding ability of the aerogel layer and the pre-oxidized silk layer, making the aerogel felt more stable and reliable during use, and not prone to problems such as stratification.
[0192] In the embodiment of the present invention, the thermal conductivity can be as low as 0.019 W / (m·K) (Example 7). In terms of thermal insulation performance, facing a high temperature of 1200°C, the back temperature of the aerogel felt in the embodiment is greatly reduced, which is about half of that in the comparative example, providing a more effective solution for high temperature protection in practical applications.
[0193] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a pre-oxidized silk aerogel felt, characterized in that: The following steps are involved: S1. Provide pre-oxidized silk felt; S2, subjecting the pre-oxidized silk felt to plasma treatment, chemical grafting, and then modification of the coupling agent to obtain the pre-treated pre-oxidized silk felt; S3, mixing tetraethyl orthosilicate, ethanol and a catalyst, stirring, then adjusting the pH value to 4-7 with sodium hydroxide or ammonia water, and then adjusting the viscosity to prepare an aerogel sol; S4, spraying aerogel sol on the pre-treated pre-oxidized silk felt to obtain an intermediate product 1; S5, immersing the intermediate product 1 in the aerogel sol to obtain the intermediate product 2; S6, gelling the intermediate product 2 to obtain the intermediate product 3; S7. The intermediate product 3 is subjected to supercritical drying treatment to obtain the final product: pre-oxidized silk aerogel felt.
2. The method for preparing the pre-oxidized silk aerogel felt according to claim 1, characterized in that: The thickness of pre-oxidized fiber felt ranges from 1mm to 20mm.
3. The method for preparing the pre-oxidized silk aerogel felt according to claim 1, characterized in that: Step S2 is specifically as follows: S2-1, plasma treatment is performed on the pre-oxidized silk felt, the plasma power is 100-500W, and the treatment time is 5-20 minutes; S2-2, adding the plasma treated pre-oxidized silk felt into a reactor, adding deionized water to immerse the pre-oxidized silk felt, and then adding 1%-5% of the mass of the pre-oxidized silk felt to the reactor (adding pure Silquest A-174 grafting agent, the added amount is 1%-5% of the pre-oxidized silk felt) and then reacting at 40-60°C for 2-4h; after the reaction is completed, taking out the pre-oxidized silk felt, washing it with deionized water, and drying it at 50-70°C for 1-4 hours; S2-3. Add the preoxidized silk felt obtained in step S2-2 into a reactor, add deionized water to immerse the preoxidized silk felt, and then add 1%-5% of the mass of the preoxidized silk felt into the reactor, and react at 40-60°C for 1-4h. After the reaction is completed, take out the preoxidized silk felt, wash it with deionized water, and dry it at 50-70°C for 1-4h to obtain the pretreated preoxidized silk felt.
4. The method for preparing the preoxidized silk aerogel felt according to claim 1, characterized in that: Step S3 is specifically as follows: According to the volume ratio of tetraethyl orthosilicate, ethanol and catalyst being 1:3-5:0.1-0.3, tetraethyl orthosilicate, ethanol and catalyst are mixed, stirred for 15-60 minutes, then the pH value is adjusted to 4-7 by sodium hydroxide, and then the viscosity is adjusted to 500-5000 mPa·s by polyethylene glycol 400 to prepare an aerogel sol; The catalyst is a hydrochloric acid solution with a mass concentration of 30-38%.
5. The method for preparing the pre-oxidized silk aerogel felt according to claim 4, characterized in that: in, The volume ratio of ethyl orthosilicate, ethanol and catalyst is 1:3:0.
1.
6. The method for preparing the pre-oxidized silk aerogel felt according to claim 1, characterized in that: The parameters for spraying the aerogel sol in step S4 are as follows: The spraying amount is controlled at 10-100 g / m2, the sprayed aerogel sol particle size is controlled at 1-50 μm, the spray angle is controlled at 30-90°, the spray speed is controlled at 5-20 m / s, and the pressure is controlled at 0.2-0.8 MPa.
7. The method for preparing the pre-oxidized silk aerogel felt according to claim 1, characterized in that: Step S5 specifically includes: immersing the intermediate product 1 in the aerogel sol for 1-3 hours at a temperature of 30-50°C.
8. The method for preparing the pre-oxidized silk aerogel felt according to claim 1, characterized in that: Step S6 specifically includes: placing the intermediate product 2 at a humidity of 40% to 60% and under an inert gas protection condition for 12 to 48 hours to perform gelation treatment, thereby obtaining the intermediate product 3.
9. The method for preparing the pre-oxidized silk aerogel felt according to claim 1, characterized in that: The parameters of the supercritical drying treatment in step S7 are as follows: drying temperature is 200-300° C., pressure is 8-15 MPa, and drying time is 2-6 hours.
10. A pre-oxidized silk aerogel felt, characterized in that: It is prepared by the method according to any one of claims 1 to 9.